2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649134
|View full text |Cite
|
Sign up to set email alerts
|

Tumor ablation at low frequencies for preferential tumor heating: Initial ex-vivo tissue studies

Abstract: Tumor ablation at frequencies lower than currently used may preferentially heat tumor tissue, preserving normal tissue at the treatment site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…In addition, the data on electrical conductivity measured in this study may be valuable in mathematical models of cancer treatment protocols that utilize tissue heating, such as RF ablation or RF hyperthermia. Furthermore, the data presented here support recent studies that have suggested that ablating hepatic tumours at lower frequencies (∼20 kHz) than currently used (∼460 kHz) could preferentially heat tumour tissue and preserve surrounding normal tissue, due to the increased difference in electrical conductivity between normal and malignant tissues at those frequencies (figure 3) Wood 2006, Schutt andHaemmerich 2008).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the data on electrical conductivity measured in this study may be valuable in mathematical models of cancer treatment protocols that utilize tissue heating, such as RF ablation or RF hyperthermia. Furthermore, the data presented here support recent studies that have suggested that ablating hepatic tumours at lower frequencies (∼20 kHz) than currently used (∼460 kHz) could preferentially heat tumour tissue and preserve surrounding normal tissue, due to the increased difference in electrical conductivity between normal and malignant tissues at those frequencies (figure 3) Wood 2006, Schutt andHaemmerich 2008).…”
Section: Discussionsupporting
confidence: 88%
“…We measured conductivity over the frequency range of 10 Hz to 1 MHz, including the standard RF ablation frequency (460 kHz). This frequency range was selected since this measurement system has been well characterized within this range (Tsai et al 2002a), and because the electrical conductivity of tumour and normal tissue at these frequencies is of current research interest Wood 2006, Schutt andHaemmerich 2008). Figure 2 shows a block diagram of the measurement system.…”
Section: Measurement Systemmentioning
confidence: 99%
“…We measured conductivity over the frequency range of 10 Hz to 1 MHz, including the standard RF ablation frequency (460 kHz). This frequency range was selected since this measurement system has been well characterized within this range (Tsai et al 2002a), and because the electrical conductivity of tumour and normal tissue at these frequencies is of current research interest (Haemmerich and Wood 2006, Schutt and Haemmerich 2008). Figure 2 shows a block diagram of the measurement system.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21] During RFA, heat generated could be attenuated in tissues using a heat sink between 0.005 and 0.01 m around the vein. 22 More research is needed to understand the properties of conductance and energy transfer of 10 per cent agar, specifically to RFA. In addition, because each individual patient is different with respect to age, fat content, water percentage, nerve distribution, and muscle development, future development of new and complex materials with similar thermal conduction by using multiple layers to more accurately demonstrate heat dispersion in human subcutaneous fat, muscle, nerve, and skin is needed.…”
Section: Discussionmentioning
confidence: 99%